Analysing news coverage in the context of Islam apostasy using Hayakawa’s Trichotomy - Siti Aishah Chu Abdullah,; Mohd Nizam Sahad,; Mohd Zulfahmi Mohamad,; Isah Umar Mainshinkafa, (Penerbit Universiti Kebangsaan Malaysia, 2024)
This study aims to conduct a descriptive content analysis to examine the coverage and potential bias regarding Islam apostasy in Harakahdaily and The Star. The analysis utilised Hayakawa’s trichotomy of general semantics three sentence types, namely reports/facts, inferences, and judgements, to assess the technical aspects of the language employed in news reporting. A comprehensive search was conducted to gather news articles on Islam apostasy published in Harakahdaily and The Star over a five-year period from 2019 to 2023. The study found that Harakahdaily had more apostasy-related articles than The Star. Moreover, being an independent newspaper, Harakahdaily used more inference and judgement statements in its headlines, implying bias. Contributors to Harakahdaily’s stories, mainly Islamic scholars and Malaysian Islamic Party (PAS) members, lack journalistic training. In contrast, The Star, a mainstream newspaper, had fewer such issues but should carefully select words to avoid misunderstandings. This study highlights how analysing news coverage of Islam apostasy using Hayakawa’s trichotomy reveals biases, stressing the need for journalists, especially those lacking training, to provide objective, unbiased information, promoting balanced reporting.